The complex tapestry of free will: striving will, indeterminism and volitional streams. - Kane, Robert (Synthese, 2019)
The aim of this paper is to respond to recent discussion of, and objections to, the libertarian view of free will I have developed in many works over the past four decades. The issues discussed all have a bearing on the central question of how one might make sense of a traditional free will requiring indeterminism in the light of modern science. This task involves, among other things, avoiding all traditional libertarian appeals to unusual forms of agency or causation (uncaused causes, noumenal selves, non-event agent causes, etc.) that cannot be accounted for by ordinary modes of explanation familiar to the natural and human sciences. Doing this, I argue, requires piecing together a "complex tapestry" of ideas and arguments that involve rethinking many traditional assumptions about free will. The paper also argues that one cannot get to the heart of historical debates about free will without distinguishing different kinds of freedom, different senses of will, and different notions of control, among other distinctions. I especially focus here on different notions of freedom and control that are necessary to make sense of free will.